2021
DOI: 10.15430/jcp.2021.26.4.277
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbial Enterotypes Differentially Respond to a High-fat Diet Based on Sex in Fischer-344 Rats

Abstract: The gut microbiota interacts with the host gut environment, which is influenced by such factors as sex, age, and host diet. These factors induce changes in the microbial composition. The aim of this study was to identify differences in the gut microbiome of Fisher-344 (F344) rats fed a high-fat diet (HFD), depending on their age and sex. Fecal microbiomes from 6-, 31-, and 74-week-old, and 2-year-old both male and female rats (corresponding to 5-, 30-, 60-, and 80-year-old humans) were analyzed using 16S rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
(56 reference statements)
2
8
0
Order By: Relevance
“…The majority of microbiomes in our set belonged to the enterotype with a low abundance of Verrucomicrobia, characteristic of Enterotype 1 (E1) in [60]. Therefore, we retained the same name for the main cluster, although we did not observe a clear dominance of Firmicutes over Bacteroidetes (Figure 3a, Supplementary Table S1), as previously reported [60].…”
Section: Rat Intestinal Microbiomes Of Two Enterotypes Responded Diff...supporting
confidence: 55%
See 3 more Smart Citations
“…The majority of microbiomes in our set belonged to the enterotype with a low abundance of Verrucomicrobia, characteristic of Enterotype 1 (E1) in [60]. Therefore, we retained the same name for the main cluster, although we did not observe a clear dominance of Firmicutes over Bacteroidetes (Figure 3a, Supplementary Table S1), as previously reported [60].…”
Section: Rat Intestinal Microbiomes Of Two Enterotypes Responded Diff...supporting
confidence: 55%
“…The Jensen-Shannon distances between samples were then calculated based on different in size and composition sets of potential marker taxa. The Calinski-Harabasz indices computed at this stage revealed variability in the optimal number of potential clusters, but using 208 genera with an abundance of ≥0.1% in at least one dataset provided the optimum with the two enterotypes (Figure 2), consistent with the two enterotypes identified in the gut microbiomes of male rats [60]. When the feeding experiment was finished, metagenomic DNA was isolated from control samples and used for 16S rRNA taxonomic analysis.…”
Section: Rat Intestinal Microbiomes Of Two Enterotypes Responded Diff...mentioning
confidence: 61%
See 2 more Smart Citations
“…[56][57][58] However, in our study, we consistently confirmed an increase in A. muciniphila after long-term administration of a HFD. 28,59 Furthermore, we found a negative correlation between the relative fecal abundance of A. muciniphila and fecal concentrations of acetic acid and butyric acid (Supplementary Fig. 3).…”
Section: High-fat Diet + G Roup Clostridium Butyricummentioning
confidence: 65%